Laparoscopic lateral suspension with mesh for apical and anterior pelvic organ prolapse: A prospective double center study. (January 2020) - Mereu, Liliana; Tateo, Saverio; D'Alterio, Maurizio Nicola; Russo, Eleonora; Giannini, Andrea; Mannella, Paolo; Pertile, Riccardo; Cai, Tommaso; Simoncini, Tommaso
Abstract: Objective: The present study analyzed long-term outcomes and complications of laparoscopic lateral suspension (LLS) with mesh to treat apical and anterior pelvic organ prolapse (POP). Study design: A prospective cohort study on 125 patients with vaginal bulge and apical +/− anterior prolapse scheduled for LLS who consecutively underwent LLS between April 2013 and January 2017 in Gynecologic Department of Santa Chiara Hospital in Trento and University of Pisa. The main outcome measure was anatomic and symptomatic POP outcome; the secondary outcomes measures were recurrence, reoperation rate, de novo posterior POP and complications. Percentage distribution of the pre- and postoperative POP-Q stages was compared at mean follow-up. Wilcoxon signed rank sum test was used to compare preoperative POP-Q stage and postoperative POP-Q stage ate mean follow up, for each patient (paired data) and for each type of prolapse. Results: 120 patients were included in the study. At 2 years 89 % of patients were asymptomatic and anatomic success rate was 94.2 % for the anterior compartment, 94.9 % for the apical compartment. Concerning posterior compartment prolapse 2 (1.7 %) patients referred stage 3 de novo prolapse during follow-up. The complication rate of Clavien-Dindo >3 was 0, 8 %. Repeat surgery for POP occurred in 6.4 % of cases. The appearance of POP-Q recurrences was concentrated at 6 months follow-up. BMI > 25 was correlated with de novo posterior compartment appearance during follow-up. Conclusions: LLS for the treatment of apical and anterior POP is a technique with optimal results in term of safety and effectiveness after 2 years follow-up.